RAISE: Reasoning Agent for Interactive SQL Exploration - Granado, Fernando F.; Lotufo, Roberto; Pereira, Jayr (Anais do Simpósio Brasileiro de Tecnologia da Informação e da Linguagem Humana (STIL); 2025: Anais do XVI Simpósio Brasileiro de Tecnologia da Informação e da Linguagem Humana, 2025)
This work proposes a novel agentic framework that unifies schema linking, query generation, and iterative refinement for text-to-SQL within a single, end-to-end component. By leveraging LLM reasoning abilities, our method emulates human database interaction: understanding data through hypothesis formation, dynamic query validation, and result-based refinement. We introduce a strategy for scaling test-time computation by increasing the depth of interactive database exploration rather than traditional approaches. Our experiments show that our agent, equipped with steps to add more diversity to the answers, achieves 81.8% Best-of-N accuracy with 8 candidate rounds, rivaling the topranked published solution (82.79%) while reducing engineering complexity.